2017
DOI: 10.1121/1.4979115
|View full text |Cite
|
Sign up to set email alerts
|

Intra-speaker and inter-speaker variability in speech sound pressure level across repeated readings

Abstract: The intra- and inter-speaker variability of speech sound pressure level (SPL) has been investigated under repeatability conditions in this work. In a semi-anechoic chamber, speech from 17 individuals was recorded with a sound level meter, a headworn microphone, and a vocal monitoring device. The subjects were asked to read twice and in sequence two phonetically balanced passages. The speech variability has been investigated for mean, equivalent, and mode SPL from each reading and device. The intra-speaker vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The uncertainty contribution of repeatability was calculated as standard deviation of the 4 repetitions of each session. Castellana et al (2017) investigated the source reproducibility by using both Voice Care and the headworn microphone. The intra-speaker variability, which represents the uncertainty contribution related to the source reproducibility of a single speaker, was quantified as the average over 17 subjects of the SPL par standard deviation of each subject, based on four repeated readings.…”
Section: Methods Reproducibility and Repeatabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The uncertainty contribution of repeatability was calculated as standard deviation of the 4 repetitions of each session. Castellana et al (2017) investigated the source reproducibility by using both Voice Care and the headworn microphone. The intra-speaker variability, which represents the uncertainty contribution related to the source reproducibility of a single speaker, was quantified as the average over 17 subjects of the SPL par standard deviation of each subject, based on four repeated readings.…”
Section: Methods Reproducibility and Repeatabilitymentioning
confidence: 99%
“…The intra-speaker variability, which represents the uncertainty contribution related to the source reproducibility of a single speaker, was quantified as the average over 17 subjects of the SPL par standard deviation of each subject, based on four repeated readings. To quantify the inter-speaker variability, that is the uncertainty contribution of a group of N speakers, researchers may refer to the standard deviation of the individual's standard deviations, i.e., s(g) in Tables II and III in Castellana et al (2017), divided by ffiffiffiffi N p . Table 1 provides the standard uncertainty contributions and the expanded uncertainty related to absolute measures and differences between measures of SPL eq , SPL m , and SPL mode , for voice monitorings detected by the two devices related to a single speaker.…”
Section: Methods Reproducibility and Repeatabilitymentioning
confidence: 99%
“…This may be related to the inherent variability in normal speech that may be more pronounced in vowel and nasalized vowel than in nasal. Previous research has also found nasalance score variability and within‐ and between‐speaker naturally occurring variations in voice and speech production. In addition, in this study, the participants was required to produce the vowel–nasal sequence in a way that was as similar to natural speech as possible without controlling for duration.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, almost all the studies have used speech materials to elicit speech in a controlled manner to study properties of speech that influence talker intelligibility. A review of literature suggests that most speech tasks used in experiments only capture a part of the changes in speech mechanism relevant to speech intelligibility such as speech sound pressure level 11 and other speech parameters due to the effect of reverberation and noise 12,55 or have been done in simulated environments. 56 With respect to classroom environments, it becomes important to study any differences observed in global speech characteristics and vowel articulation characteristics of talkers from real classroom environments, when exposed to different room acoustical conditions and when using the natural mode of speech delivery, that is, lecturing.…”
Section: Global Speech Characteristicsmentioning
confidence: 99%
“…7 Differences in vocal effort are seen between conversational task and when speaking in a classroom environment. 8 While it is widely acknowledged that talkers greatly vary in their intelligibility through speech modifications in terms of their speech sound pressure levels, pitch and durational measures that happen due to changes in speech production and delivery, 9,10 reading material, 11 environment, 8 and reverberation, 12 these studies have either utilized speech samples extracted during reading standard pre-administered texts or conversational tasks and when speaking in controlled environments. There have been no studies on how talkers articulate their speech in real classroom environments using samples from natural free-flowing lectures.…”
Section: Introductionmentioning
confidence: 99%